Prevalence of smoking among psychiatric patients in outpatient department of tertiary care centre: A descriptive cross-sectional study - Sharma, Sandesh; Uprety, Saroj; Sharma, Sadikshya; Ghimire, Apekshya; Pant, Biswas (Journal of Psychiatrists’ Association of Nepal, 2023)
Background: Even though psychiatric illness is a risk factor of smoking tobacco; only few studies have been conducted to estimate the prevalence of smoking among that patient group in Nepal. Our study aims to determine the prevalence of smoking among psychiatric patients in the outpatient department of tertiary care centre. Material and Method: A descriptive cross-sectional study was conducted in the psychiatric outpatient department of a tertiary care centre from 27th March to 27th May, 2022 following ethical approval from the Institutional Review Committee (Reference number: 577/078-079). A convenience sampling technique was used to include 398 patients, who were assessed for tobacco use behaviour using a semi-structured questionnaire and nicotine dependence using the Fagerstrom Test for Nicotine Dependence instrument. Data was collected using the “KoBo toolbox” Android mobile application and analysed using Microsoft Excel, Statistical Package for Social Sciences version 25.0, and R Studio. Point estimates and 95% confidence intervals were calculated. Results: The prevalence of current smokers was 104 (26.13%) (21.88-30.74 at 95%CI). The prevalence of past smokers was 48 (12.06%) (9.03-15.67 at 95% CI). Nicotine dependence was present in 75(72.12%) of the 104 current smokers and 40 (83.33%) among 48 past smokers. Conclusion: Our study found a lower prevalence of smoking among participants compared to other similar studies conducted at the national level.